2017
DOI: 10.1186/s12889-017-4422-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dog ownership on objective measures of free-living physical activity and sedentary behaviour in community-dwelling older adults: a longitudinal case-controlled study

Abstract: BackgroundThere is some evidence to suggest that dog ownership may improve physical activity (PA) among older adults, but to date, studies examining this, have either depended on self-report or incomplete datasets due to the type of activity monitor used to record physical activity. Additionally, the effect of dog ownership on sedentary behaviour (SB) has not been explored. The aim of the current study was to address these issues by using activPAL monitors to evaluate the influence of dog ownership on health e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 36 publications
4
85
1
1
Order By: Relevance
“…It was positively associated with expanding participants' life space and was associated with them feeling more physically and socially active. Consistent with previous literature [17] dog walking indeed facilitates increases in physical activity. However, we also found that dog walking was positively associated with meeting more people, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…It was positively associated with expanding participants' life space and was associated with them feeling more physically and socially active. Consistent with previous literature [17] dog walking indeed facilitates increases in physical activity. However, we also found that dog walking was positively associated with meeting more people, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Sitting time accumulation data was derived by identifying all sitting bouts during waking, worn time on valid days, and calculating the cumulative sitting time (in minutes and as a proportion of total sitting time) occurring in bouts of any duration. Outcome measures were calculated from the activPAL monitor using a custom Excel macro as per Dall et al [49].…”
Section: Activpal Data Processingmentioning
confidence: 99%
“…However, when further explanatory variables (demographic, socioeconomic factors, medical condition) were added to the analysis, the difference between dog owners and non-dog owners was attenuated but still significant (p < 0.05), with dog owners still more active than non-dog owners. In addition to duration of walking, Dall et al (2017) found that when dog owners were compared with non-dog owners, dog owners walked significantly more steps per day (p < 0.001), spent more time walking per day (p < 0.001), and spent more time walking at a moderate cadence per day (p < 0.001). Research supports the value of dogs in promoting physical activity in older adults.…”
Section: Animals and Physical Activitymentioning
confidence: 99%